2014
DOI: 10.1371/journal.pone.0087617
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of CD80 in HSV Targets the Recombinant Virus to PD-L1 on DCs and Allows Productive Infection and Robust Immune Responses

Abstract: CD80 plays a critical role in stimulation of T cells and subsequent control of infection. To investigate the effect of CD80 on HSV-1 infection, we constructed a recombinant HSV-1 virus that expresses two copies of the CD80 gene in place of the latency associated transcript (LAT). This mutant virus (HSV-CD80) expressed high levels of CD80 and had similar virus replication kinetics as control viruses in rabbit skin cells. In contrast to parental virus, this CD80 expressing recombinant virus replicated efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 64 publications
5
43
1
Order By: Relevance
“…In addition, T cell exhaustion was blocked by a recombinant HSV-1 strain expressing CD80 that binds to PD-L1 on the surfaces of DCs (32). Overall, our previous and current findings suggest that CD8␣ ϩ DCs contribute to increased HSV-1 latency and T cell exhaustion (17,22,25,26,28,32). Our previously published studies with regard to the role of LAT in T cell exhaustion were done with mice.…”
Section: Fig 3 Isolation and Functionality Of Purified Cd8 ϩ T Cells supporting
confidence: 66%
See 3 more Smart Citations
“…In addition, T cell exhaustion was blocked by a recombinant HSV-1 strain expressing CD80 that binds to PD-L1 on the surfaces of DCs (32). Overall, our previous and current findings suggest that CD8␣ ϩ DCs contribute to increased HSV-1 latency and T cell exhaustion (17,22,25,26,28,32). Our previously published studies with regard to the role of LAT in T cell exhaustion were done with mice.…”
Section: Fig 3 Isolation and Functionality Of Purified Cd8 ϩ T Cells supporting
confidence: 66%
“…Previously, we showed that LAT expression and increased latency correlate with T cell exhaustion (17,22,26,32). We also demonstrated that latency in PD-1 Ϫ/Ϫ mice was lower than that in their wt counterparts (17).…”
Section: Lack Of Effect Of Adoptively Transferred Cd8mentioning
confidence: 60%
See 2 more Smart Citations
“…We performed sitespecific mutagenesis within the gK 8mer region and inserted the complete open reading frame (ORF) of the mutated form of the gK gene into both copies of the latency-associated transcript (LAT) regions and under the LAT promoter as we described previously (34,(37)(38)(39)(40). Since suitable antibodies for detection of gK are not available, we inserted the myc epitope tag in-frame at the 3= end of the mutated gK ORF for identification of the inserted gK.…”
mentioning
confidence: 99%